Becoming a digital citizen in Estonia? New migrants’ interpretations of their digital participation - Allaste, A.-A.; Cairns, D. (Journal of Applied Youth Studies, 2025)
‘Digital citizenship’ can be seen both as an aspect of and precursor to participation in society. Potentially, this might create new opportunities and encourage participation among different groups, including new migrants. The political participation of exchange students, in many cases living in another country temporarily, has not been extensively studied previously. This article focuses on both secondary school and university students and their approaches to becoming digital citizens in Estonia. Using evidence from qualitative interviews, the article analyses the meanings they give to their experiences of integrating into Estonian society with a focus on take-up of digital opportunities, with fieldwork conducted between October 2021 and April 2022, when society remained partly closed. The analysis confirms the importance of having access to various E-services and the transparency of state bureaucracy, which help increase trust and encourage participation. However, the conditions for participating and self-perception as a (digital) citizen are highly dependent on the ability to engage in civic debate in the host society and integrate into social networks in Estonia, issues that could be better addressed in digital environments.